Salt reduction in different bread types: an intervention study in the Northern Portugal - Nascimento, A. (2018)
Salt consumption in Portugal almost doubles WHO recommended maximum level of intake and bread consumption represents 18% of daily salt intake. The aim of this study was to evaluate sodium and correspondent salt levels in Portuguese bread before and after an intervention planned to reduce salt contents, to motivate representative associates of the Northern Portugal Bakery Association (AIPAN) to voluntary reduce salt in bread. Sampling plan included 220 samples of 4 traditional bread types: carcaça, regueifa, broa, pão da avó, collected from two bakeries (control or intervention) per district, from five different districts (Viana do Castelo, Vila Real, Braga, Porto, Aveiro), between July and November 2016. After initial quantification (baseline), the intervention group carried out an intervention directed at the bakery owner in order to decrease the salt content in the recipe of the four types of bread, without other change in industrial process. Sodium levels were determined using an Inductively Couple Plasma Atomic Emission Spectrometry–ICP-OES. Analyses were performed in quality management system according to ISO 17025. Differences between groups were assessed with t test, and tests with a P-value of <0.05 were considered statistically significant. Baseline values are in line with the Portuguese law. Mean salt values were: carcaça 1.23g, pão da avó 1.13g, broa 1.05g and regueifa 1.22g. Post-Intervention, salt levels decreased (p-values <0.05) in the four types of bread. Since bread has the highest individual contribution to salt intake, any reduction in salt levels in bread will be equivalent to a significantly decrease of sodium intake in society. Reducing salt levels in bread, without further changes in the production process, would bring important economic and public health benefits, especially related to cardiovascular diseases and hypertension. The outcome of this study provides baseline information to police makers to implement a strategy to reduce salt in bread.